Inhibition of TGF-β Signaling in SHED Enhances Endothelial Differentiation. (February 2018) - Xu, J.G.; Gong, T.; Wang, Y.Y.; Zou, T.; Heng, B.C.; Yang, Y.Q.; Zhang, C.F.
Low efficiency of deriving endothelial cells (ECs) from adult stem cells hampers their utilization in tissue engineering studies. The purpose of this study was to investigate whether suppression of transforming growth factor beta (TGF-β) signaling could enhance the differentiation efficiency of dental pulp–derived stem cells into ECs. We initially used vascular endothelial growth factor A (VEGF-A) to stimulate 2 dental pulp–derived stem cells (dental pulp stem cells and stem cells from human exfoliated deciduous teeth [SHED]) and compared their differentiation capacity into ECs. We further evaluated whether the vascular endothelial growth factor receptor I (VEGF-RI)-specific ligand placental growth factor-1 (PlGF-1) could mediate endothelial differentiation. Finally, we investigated whether the TGF-β signaling inhibitor SB-431542 could enhance the inductive effect of VEGF-A on endothelial differentiation, as well as the underlying mechanisms involved. ECs differentiated from dental pulp–derived stem cells exhibited the typical phenotypes of primary ECs, with SHED possessing a higher endothelial differentiation potential than dental pulp stem cells. VEGFR1-specific ligand-PLGF exerted a negligible effect on SHED-ECs differentiation. Compared with VEGF-A alone, the combination of VEGF-A and SB-431542 significantly enhanced the endothelial differentiation of SHED. The presence of SB-431542 inhibited the phosphorylation of Suppressor of Mothers Against Decapentaplegic 2/3 (SMAD2/3), allowing for VEGF-A-dependent phosphorylation and upregulation of VEGFR2. Our results indicate that the combination of VEGF-A and SB-431542 could enhance the differentiation of dental pulp–derived stem cells into endothelial cells, and this process is mediated through enhancement of VEGF-A-VEGFR2 signaling and concomitant inhibition of TGF-β-SMAD2/3 signaling.